First Isolation and Molecular Characterization of Chicken Astrovirus and Avian Nephritis Virus in Chickens in Bangladesh - Ali, Md Zulfekar; Moula, Mohammad Moktader; Bhuiyan, Zafar Ahmed; Giasuddin, Md; Shin, Hyun-Jin (Frontiers in Veterinary Science, 2021)
Chicken astrovirus (CAstV) and avian nephritis virus (ANV) are enteric viruses of poultry and have infected a wide range of poultry species worldwide, causing runting-stunting syndrome (RSS), which requires virus screening and results in serious economic damage. No confirmed cases have been reported from Bangladesh. In the present study, CAstV and ANV were monitored in Bangladesh. We monitored samples for CAstV and ANV and compared their genomic sequences to other reference strains. We found 8/31 flocks (25.8%) were positive for CAstV, 6/31 flocks (19.3%) had mixed infection of CAstV and ANV, and 1 flock (3.2%) was positive for ANV. Only ANV and a combination of CAstV and ANV were found in broilers and broiler breeders, but CAstV was found in all types of chickens. We isolated two of each from CAstV and ANV through specific pathogen-free chicken embryonated eggs via the yolk sac route. Phylogenetic analysis based on the ORF1b conserved region of CAstV and ANV suggested that the locally circulating strain was closely related to the strains isolated from India and Brazil. This report is the first molecular characterization of CAstV and ANV in Bangladesh. This study highlights that CAstV and ANV are circulating in Bangladeshi poultry.